2007
DOI: 10.1007/s00213-007-0736-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-motivational predictors of excessive drinkers’ success in changing

Abstract: It was concluded that (a) both cognitive and motivational factors affect the likelihood of drinking reductions and (b) a complete understanding of drinking problems should be formulated in terms of both cognitive and motivational variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 43 publications
5
78
0
3
Order By: Relevance
“…Given the potential role of attentional bias in the maintenance of addictive behaviours (e.g. Cox et al, 2007), this result is intriguing: attempting to limit food intake may actually be counterproductive. However, the results also suggested that dieters may have lower FAB than high restrained non-dieters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential role of attentional bias in the maintenance of addictive behaviours (e.g. Cox et al, 2007), this result is intriguing: attempting to limit food intake may actually be counterproductive. However, the results also suggested that dieters may have lower FAB than high restrained non-dieters.…”
Section: Discussionmentioning
confidence: 99%
“…That is, they will direct their attention towards such information and process it more extensively. Attentional bias is important since it may contribute to the maintenance and/or escalation of the addictive behaviour (e.g., Cox, Pothos & Hosier, 2007).…”
mentioning
confidence: 99%
“…also Cox, Pothos & Hosier, 2007). In the present study we examine the evidence that a corresponding result might be possible in eating behavior.…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, prospective neuroimaging studies modelling relapse vulnerability and future drug use have shown that reduced attention toward drug-related cues 11,12,[28][29][30] and increased attention toward non-drug-related reinforcers [31][32][33] predicted longer abstinence durations in individuals with substance use disorders. Although these studies are highly informative, many have been limited to the cross-sectional Background: Increased attention bias toward drug-related cues over non-drug-related intrinsically pleasant reinforcers is a hallmark of drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…24 Importantly, cross-sectional studies have shown that the LPP amplitude to drug-related cues is decreased 25,26 while that to non-drug-related cues is increased 19,27 after a period of reduced drug use (3 d to about 1 yr). Moreover, prospective neuroimaging studies modelling relapse vulnerability and future drug use have shown that reduced attention toward drug-related cues 11,12,[28][29][30] and increased attention toward non-drug-related reinforcers [31][32][33] predicted longer abstinence durations in individuals with substance use disorders. Although these studies are highly informative, many have been limited to the cross-sectional effects of shorter-term 19 or longer-term abstinence 25,31 relying mostly on self-reported follow-up assessments.…”
Section: Introductionmentioning
confidence: 99%